The Sovereign Default Problem in the Eurozone: An Insurance-Based Approach - Nadjeschda Arnold; Ray Rees (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper argues that the Eurozone crisis stems from a risk management failure in the Eurosystem's design, and that applying insurance theory is useful. We model risk neutral agents choosing portfolios of government bonds of n countries in a monetary union and other assets. We firstly analyse a country's debt choice, assuming as a benchmark case that the no-bailout threat is credible, accounting for the effect on its equilibrium interest rate, and then establish an equally efficient mutual insurance fund covering accruing indemnities almost certainly. We also discuss necessary institutional arrangements and other proposals in the light of our results.
Keywords: G11; G12; G22; H63; H77; 330; European debt crisis; sovereign debt; bailout; monetary union; debt management